Analysis of the service needs of outpatients undergoing thyroid fine needle aspiration biopsy based on the Kano model - Xiaoqin Wang; Chuanfeng Pei; Chao Jia; Long Liu; Hongmei Liang (BMC Nursing)
Abstract Background Thyroid nodules are common, and fine needle aspiration biopsy (FNAB) is essential for diagnosis and treatment. Patients’ service needs are rarely addressed and discussed. This study was to analyze the nursing service needs of patients undergoing outpatient thyroid FNAB. Methods Using the Delphi method, indicators of nursing service needs were established. A survey based on the Kano model was conducted from February to May 2024 to analyze service needs among patients undergoing thyroid FNAB. A quadrant analysis chart was used to visualize the impact of service characteristics on patient satisfaction. Results Among the 32 service needs, 12 items were in the improved category, 10 items were in the advantage category, 9 items were in the reserved category, and 1 item was in the observation category. Conclusions The Kano model effectively categorizes the service needs of outpatients undergoing thyroid FNAB, guiding healthcare providers to enhance patient satisfaction through optimized services. Trial registration The registration number is ChiCTR2400080522, and the registration date is January 30, 2024.